2017
DOI: 10.1158/1541-7786.mcr-16-0366
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3σ Contributes to Radioresistance By Regulating DNA Repair and Cell Cycle via PARP1 and CHK2

Abstract: 14-3-3σ has been implicated in the development of chemo and radiation resistance and in poor prognosis of multiple human cancers. While it has been postulated that 14-3-3σ contributes to these resistances via inhibiting apoptosis and arresting cells in G2/M phase of the cell cycle, the molecular basis of this regulation is currently unknown. In this study, we tested the hypothesis that 14-3-3σ causes resistance to DNA-damaging treatments by enhancing DNA repair in cells arrested in G2/M phase following DNA-dam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
3
21
0
1
Order By: Relevance
“…Through interaction with the target proteins, 14‐3‐3 proteins including SFN alter the activity, modifications, and intracellular localization of ligands . In particular, SFN regulates DNA repair factors such as DNA‐PKcs, when DNA is damaged by chemotherapy or radiotherapy in human cancer . Based on the previous report, we assume that the high number of gene mutations in Tg‐SPC‐SFN +/− tumors might be due to binding with unknown factor(s), which is associated with the DNA repair system.…”
Section: Discussionmentioning
confidence: 93%
“…Through interaction with the target proteins, 14‐3‐3 proteins including SFN alter the activity, modifications, and intracellular localization of ligands . In particular, SFN regulates DNA repair factors such as DNA‐PKcs, when DNA is damaged by chemotherapy or radiotherapy in human cancer . Based on the previous report, we assume that the high number of gene mutations in Tg‐SPC‐SFN +/− tumors might be due to binding with unknown factor(s), which is associated with the DNA repair system.…”
Section: Discussionmentioning
confidence: 93%
“… Cell cycle arrest. Following the IR-induced DNA damage detection, molecules in the cell cycle checkpoints can regulate and arrest cell cycle progression, and 14–3-3σ, a member of 14–3-3 protein family, was shown to be closely associated with the radioresistance development by arresting cancer cells in the G2/M phase [ 41 ]. Moreover, tumor cells can utilize two distinct kinase signaling cascades for the DNA damage repair here, including ATM-Chk2 and ATR-Chk1 axes [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…GO and KEGG enrichment analysis results showed that the 558 PCGs co-expressed with LINC01600 were involved in various biological processes such as DNA damage repair, metabolism, cell cycle, and so on. Many studies have shown that DNA damage repair, metabolism, and cell cycle are highly correlated with radiosensitivity (30)(31)(32)(33)(34). This further indicates that LINC01600 and the PCGs co-expressed with it are associated with radioresponse.…”
Section: Discussionmentioning
confidence: 92%